Implementasi Framework Objective and Key Results (OKR) pada Startup TimbangIN - Meikal, Rochmat; Artana, I Made; Paramitha, A.A Istri Ita (STMIK Banjarbaru, 2024)
TimbangIN is a starup that operates in the field of buying and selling recycled waste such as cardboard, paper, iron, aluminium, copper and more else. TimbangIN still running according to its bussines model, but does not yet have a focused goal to achieve so TimbangIN has not been able to develop well. Implemented OKR for 6 months with the specified objective, namely Managing TimbangIN so that it can survive in the sense that income is greater than expenses and there are 2 key results with income targets and the amount of waste collected, increasing targets is carried out in OKR literacy. The results obtained from implementing the OKR framework were that in the first 3 month it got a value of 0,9, which means achieved the goal and in the 3 months of literation got a value of 1.0 which means the goals have been achieved maximally.Keywords: Framework; Objective and Key Results; Startup Â AbstrakTimbangIN merupakan sebuah startup yang bergerak di bidang jual-beli sampah daur ulang seperti kardus, kertas, besi, aluminium, tembaga dan lain sebagainya. TimbangIN masih berjalan sesuai model bisnisnya, namun belum memiliki fokus tujuan yang ingin dicapai sehingga TimbangIN belum bisa berkembang dengan baik. Diterapkan framework Objective and Key Results (OKR) selama 6 bulan dengan Objective yang ditentukan yaitu Mengelola TimbangIN agar dapat tetap survive dalam artian pendapatan lebih besar dari pengeluaran biaya dan terdapat 2 key results dengan target pendapatan serta jumlah sampah yang terkumpul, peningkatan target dilakukan pada iterasi OKR. Hasil yang diperoleh dari pengimplementasian framework OKR yaitu pada 3 bulan pertama memperoleh nilai 0,9 yang berarti telah mencapai tujuan dan pada 3 bulan iterasi memperoleh nilai 1,0 yang berarti goals telah tercapai dengan maksimal.Â Â